Responsiveness, Performance and Corruption: Reasons for the Decline of Political Trust - Torcal, Mariano; Christmann, Pablo (Frontiers in Political Science, 2021)
We test the importance of responsiveness, performance and corruption to explain the evolution of political trust in Spain between 1997 and 2019. To this end, the study analyses two longitudinal datasets, namely, a repeated cross-sectional dataset from the Spanish samples of Eurobarometer and an individual-level panel survey conducted during a period of economic recovery in 2015. The study finds that perceptions about political corruption and responsiveness matter greatly in shaping political trust and to a lesser extent economic performance. Although the Great Recession is likely responsible for the sharp decline in trust towards political parties and the parliament between 2008 and 2012, the analysis suggests that trust in representative institutions remains low even after the Recession because of a series of devastating corruption incidents and a perceived lack of responsiveness of the political system. On the other hand, the study finds indications that trust in the judicial system might have been mainly affected by perceptions of corruption.